2010
DOI: 10.1007/s10706-010-9363-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness and Warning Systems for Populations with Special Needs: Ensuring Everyone Gets the Message (and Knows What To Do)

Abstract: The recent South Asian Tsunami has brought world-wide awareness to the effects of major disasters upon all segments of society. Vulnerable populations such as the disabled, children, or the elderly are at particular risk in a disaster and it is vital to consider their special needs in the design of disaster preparedness and warning systems. Additionally, tourists, recent immigrants, and refugees face challenges when confronted with disaster in unfamiliar locations, linguistically isolated, and in need of assim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 4 publications
0
8
0
3
Order By: Relevance
“…Rooney and White [ 122 ] note that people with a disability have been left behind in emergency situations because they were not assisted or accommodated within building and emergency plans. In relation to accessing information, current emergency communication networks do not take into account people with a hearing disability and those with vision impairment [ 123 ]. In relation to evacuation, most evacuation plans require people to be able to walk, drive, see, or hear and thus are not accessible by people with disabilities [ 124 ], which means many cannot evacuate under current systems.…”
Section: Vulnerable Groups and The Roles Of Animals In Their Livesmentioning
confidence: 99%
“…Rooney and White [ 122 ] note that people with a disability have been left behind in emergency situations because they were not assisted or accommodated within building and emergency plans. In relation to accessing information, current emergency communication networks do not take into account people with a hearing disability and those with vision impairment [ 123 ]. In relation to evacuation, most evacuation plans require people to be able to walk, drive, see, or hear and thus are not accessible by people with disabilities [ 124 ], which means many cannot evacuate under current systems.…”
Section: Vulnerable Groups and The Roles Of Animals In Their Livesmentioning
confidence: 99%
“…Using specific and simplified language is one way. Ensuring the accuracy and cultural acceptance of the translated materials is another way since even the simplest weather icon can be interpreted differently by different cultures (Andrulis, Siddiqui, & Gantner 2007;Sullivan & Hakkinen, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers and practitioners have given attention to vulnerable populations who request special assistance during times of risk communication. Vulnerable populations include not only mentally or physically disabled individuals but also immigrants, refugees, elderly, children, and other linguistically, socially, geographically, or economically disadvantaged individuals who have difficulties receiving and responding to warnings, including emergency preparation messages (Sullivan & Hakkinen, 2011). Findings from Andrulis, Siddiqui, and Gantner study (2007) indicated that major government and non-government agencies had taken efforts to disseminate disaster preparedness and response information in multiple languages to the minority communities through multiple communication channels (e.g., internet, community radio station).…”
Section: H Xin a Karamehic-muratovic And D Cluphfmentioning
confidence: 99%
“…First of all, it is necessary to warn the population and to notify specific persons by activating the warning and notifying network. As Sullivan et al (2011) points out, these networks ultimately support the rescue work and they are elemental parts of the reaction phase. Technical means for warning and notification may be of a different character.…”
Section: Introductionmentioning
confidence: 95%